PENERAPAN SISTEM MANAJEMEN KUALITAS AIR PADA KOLAM PEMELIHARAAN IKAN NILA MASYARAKAT DALAM MENDUKUNG PENGEMBANGAN PERIKANAN BUDIDAYA SKALA KECIL DI DESA MAFFA, HALMAHERA SELATAN - Findra, Muhammad Nur; Samadan, Gamal M.; Putranti, Oktora Dwi; Supyan, Supyan; Duwila, Aryo; Saputra, Adam Dwi (Jurnal Abdi Insani, 2024)
Small-scale fisheries generally refer to fisheries activities carried out by individuals or small groups using simple equipment and relatively small production capacity compared to large commercial fisheries. It has many obstacles and challenges faced by the perpetrators, including the technology used tends to be very simple. The same problem is also faced by tilapia farmers in Maffa Village, East Gane District, South Halmahera Regency. This community service activity aimed to implement an effective water quality management system in community tilapia rearing ponds, especially small-scale ones in Maffa Village. The activity was carried out in August-September 2024. The stages of activity implementation start from the preparation stage by the implementation team, socialization of activities, counseling to target partners in the form of delivering material related to the topic of activities, implementing the technology of aquaculture pond water quality management systems, and evaluation. The result of this activity is the implementation of counseling activities on effective water quality management systems in aquaculture ponds. In addition, the application of technology in the form of an aeration system was also well implemented, where the target partners' aquaculture ponds currently use a blower equipped with a diffusser to supply dissolved oxygen in the pond. The evaluation of the activity showed that more than 80% of the target partners understood and had skills in the application of this technology, where 81.82% of the cultivator group members understood the material about the technology applied and 90.91% actively participated and had skills in the technology application activities carried out. In conclusion, this activity has been successfully carried out in the form of counseling and the availability of aeration systems in the target partners' tilapia farming ponds.